1988
DOI: 10.1016/0887-6177(88)90046-7
|View full text |Cite
|
Sign up to set email alerts
|

A survey of common misconceptions about head injury and recovery

Abstract: A survey questionnaire composed of 25 statements about head injury and recovery was administered to 221 individuals at a large regional shopping mall. Survey items were categorized into domains pertaining to the use of seatbelts, the nature of unconsciousness, the nature of amnesia, characteristics associated with brain injury, and recovery from brain injury. An additional 8 survey items inquired about the sources from which people obtained their knowledge, extent of personal experience with brain injury, occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(113 citation statements)
references
References 0 publications
5
107
1
Order By: Relevance
“…The results of this study show that misconceptions about brain injury that have been endorsed in several studies conducted in the US and Canada [4,6,8,9] are also endorsed by the general public in Britain. Indeed, the magnitude of misconceptions held by respondents in the present study were on the whole markedly greater than those Hargrave [15] showed that although the British public accept this tenet and do not expect to be educated through these medium, they do expect a degree of verisimilitude especially pertaining to medical issues.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The results of this study show that misconceptions about brain injury that have been endorsed in several studies conducted in the US and Canada [4,6,8,9] are also endorsed by the general public in Britain. Indeed, the magnitude of misconceptions held by respondents in the present study were on the whole markedly greater than those Hargrave [15] showed that although the British public accept this tenet and do not expect to be educated through these medium, they do expect a degree of verisimilitude especially pertaining to medical issues.…”
Section: Discussionmentioning
confidence: 60%
“…Gouvier et al [4] developed a questionnaire consisting of 25 statements designed to examine knowledge about brain injury. They found that almost half of their sample held misconceptions relating to the nature of unconsciousness, the recovery process and the impact of brain injury on cognitive status.…”
Section: Introductionmentioning
confidence: 99%
“…Memory dysfunction is a common complaint following brain injury 1,26,33) . There are several known organic memory dysfunction patterns 6,38) , but malingers frequently lack sufficient knowledge to mimic true memory disorder symptoms and are likely to over-portray impairment severity or produce improbable assessment outcomes that are inconsistent with those of cooperative brain-injured patients 8,28) . The DE group did not show malingered memory dysfunctions patterns, i.e., the same or lower recognition performance than recall performance 41) , but did show lower effort on the performance of the effortful task of recall memory.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen true-false statements about TBI knowledge and 16 true-false statements about concussion knowledge were offered. The researchers synthesized the survey instrument from past studies on TBI knowledge and misconceptions; the TBI knowledge items are identical to the validated questionnaire used by Hux et al (2013) and Evans et al (2009), which was adapted from the original questionnaire by Gouvier et al (1988). The 16 concussion statements are identical to the validated survey of concussion knowledge used by Duff and Stuck (2015).…”
Section: Setting and Instrumentationmentioning
confidence: 99%
“…The researchers dispensed a survey designed to evaluate accuracy of TBI beliefs to members of the lay public, and participants responded using a 4-point Likert scale to endorse or reject each item. Items pertaining to unconsciousness, memory loss, and recovery were commonly missed (Gouvier et al, 1988). Forty-one percent of respondents believed that "Even after several weeks in a coma, when people wake up, most recognize and speak to others right away" (Gouvier et al, 1988, p. 335); over 80% 7 believed that "People can forget who they are and not recognize others but be normal in every other way" (Gouvier et al, 1988, p. 336); over 70% incorrectly denied that "People who have had one head injury are more likely to have a second one" (Gouvier et al, 1988, p. 336); and 46% believed that "Sometimes a second blow to the head can help a person remember things that were forgotten " (Gouvier et al, 1988, p. 336).…”
Section: Rehabilitationmentioning
confidence: 99%